HERMENEUTICS OF THE HOLY RELIGION TEXTS (The Study of the Relationship of the Qur'anic Text to Religious Life) - Lubis, Zakaria Husin (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2020)
The discourse on the discussion of the holy book experiences lengthy debates in every religion because the holy book is a representation of the life guidelines adopted by religious people. From the beginning of its creation, humans tend to have a primordial promise of a power beyond their means. The promises have been written in the holy book to be obeyed, but the problem is when they try to understand what is written in the holy book, therefore many commentators try to interpret this scripture according to the knowledge they understand. The efforts of interpreters in understanding this holy book eventually made them divided into several groups. The group of interpreters who want the interpretation of the scriptures contextually using the hermeneetic method, interpreters who understand textually by fundamentalists, interpreters who want the separation between text and the world. With a variety of different ways of understanding this eventually becomes polemic in society because of the influence of this scripture that varies in translation. As for the writing method used is qualitative with historical and phenomenological approaches. The author tries to sort events according to the period of years, from the appearance of the early writings or ancient texts to the contemporary period.